An assessment of global microfinance models and lessons for muslim practitioners (2007)
Poverty is widespread the world over and Microfinancing is one of the ways by which it can be reduced. There are different models of microfinance. This paper examines some microfinance institutions as practiced in selected countries with a view to adopting some of their innovative and novel approaches to the emerging Islamic microfinance industry. Analysts have concentrated their efforts on examining the workings of microfinance models without drawing lessons from the various conventional models of Microfinance in relation to that of Islam. Hence, this paper examines each of the models and draws out areas that can conveniently match with and foster the Islamic model. It does a content analysis of primary and secondary sources of works on Microfinancing.